Changing Lives in the Nile Basin - World Bank Group (World Bank, Entebbe, 2016)
A remarkable program of cooperation in the Nile basin is bringing change to millions of people living in poverty. By promoting trust and cooperation between the 10 Nile countries, the Nile basin initiative (NBI) has enabled these countries to advance a shared vision for development of the region based on sustainable management and equitable use of the Nile water resources. Countries have come together to plan and implement development projects that are proving to be transformative in terms of food, water, and energy security - as well as improving the resilience of some of the poorest in society. Once implemented, these projects promise to benefit nearly 30 million people.